2011
DOI: 10.1111/j.1537-2995.2011.03137.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of blood components separated from donated whole blood after an overnight holding at room temperature with the buffy coat method

Abstract: These data suggest that blood components (RBCs, pooled PCs, and FP) separated from WB that has been stored overnight at room temperature by the BC method are of acceptable quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 33 publications
(53 reference statements)
1
21
2
Order By: Relevance
“…Swirling, which is the ability of functional discoid platelets to align to a current in the storage medium, was not different. Others found a higher CD62P expression and annexin A5 binding at onset for platelet concentrates from 8-vs 24-hour-held whole blood, but this difference disappeared on day 3 [36]. In this study, platelet yield was 14% lower in the 8-hour hold group.…”
Section: Effect Of Whole Blood Holding Time On the Quality Of Buffy Ccontrasting
confidence: 73%
See 3 more Smart Citations
“…Swirling, which is the ability of functional discoid platelets to align to a current in the storage medium, was not different. Others found a higher CD62P expression and annexin A5 binding at onset for platelet concentrates from 8-vs 24-hour-held whole blood, but this difference disappeared on day 3 [36]. In this study, platelet yield was 14% lower in the 8-hour hold group.…”
Section: Effect Of Whole Blood Holding Time On the Quality Of Buffy Ccontrasting
confidence: 73%
“…Our group found a decline in factor III:C from 1.22 ± 0.31 IU/mL when processed within 2 hours of collection vs 1.05 ± 0.25 IU/mL when processed after 16 to 20 hours (14% lower; P b .001) [14]; others found no difference in factor V and a 33% or 12% lower value for factor VIII, in a study that reported the results of 2 processing sites [19]. An evaluation of 9 clotting factors showed the same pattern as others [36]. Finally, a multisite study of the BEST Collaborative [52] demonstrated a 6% lower protein C and a 14% lower protein S, but no change in antithrombin for whole blood held for 24 to 26 vs less than 8 hours in a paired study; factor VIII was 23% lower.…”
Section: Effect Of Holding Time On the Quality Of Plasmasupporting
confidence: 65%
See 2 more Smart Citations
“…In our study we found that findings were not statistically significant [11]. Another similar study done by Lu et al [12] revealed that the platelet yield in PCs prepared from an overnight-hold WB sample was significantly higher, while CD62P expression and annexin V binding were lower (p \ 0.05). These findings were comparable with our results.…”
Section: Discussioncontrasting
confidence: 55%